Changes in subgingival microflora in patients with fixed orthodontic appliances - Adriana ARBUTINA; Irena Kuzmanović RADMAN; Mirjana UMIĆEVIĆ-DAVIDOVIĆ; Marijana ARAPOVIĆ-SAVIĆ; Aleksandra ĐERI; Radmila ARBUTINA; Saša MARIN; Renata JOSIPOVIĆ; Nataša TRTIĆ (Dental Press Journal of Orthodontics)
ABSTRACT Introduction: Fixed orthodontic therapy is often accompanied by accumulation of plaque around the orthodontic brackets, which increases the number of periodontopathogenic bacteria. Objective: The objective of this study was to determine the changes in the subgingival microflora that occurred six months after the placement of a fixed orthodontic appliance. Methods: The study included 30 patients aged 13 to 35 years, in whom samples of subgingival plaque were taken before and six months after the start of fixed orthodontic therapy from the disto-buccal subgingival space of the left upper (U1) and lower central incisors (L1), mesio-buccal subgingival space of left upper (U6) and lower (L6) first molars. Material samples were tested for the presence of the following bacteria: Tannarela forsythia, Treponema denticola, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Prevotella intermedia, Prevotella nigrescens and Eikenella corrodens, using the PCR method. Results: A significant increase of patients with presence of bacteria especially in the molar region was found: Tannarela forsythia (U6 T1 10%-T2 80%, L6 T1 16.67%-T2 80%), Porphyromonas gingivalis (U6 T1 60%-T2 90%, L6 T1 60%-T2 83.33%), Prevotella intermedia (U6 T1 23.33%-T2 73.33%, L6 T1 26.67%-T2 76.67%), Prevotella nigrescens (U6 T1 16.67%-T2 63.33%, L6 T1 23.33%-T2 73.33%) and Eikenella corrodens (U6 T1 26.67%-T2 63.33%, L6 T1 23.33%-T2 73.33%) six months after the placement of the fixed orthodontic appliance. Conclusion: In the initial phase of fixed orthodontic therapy, an increase in the number of patients with periodontopathogenic bacteria Tannarela forsythia, Treponema denticola, Porphyromonas gingivalis, Prevotella intermedia, Prevotella nigrescens and Eikenella corrodens was observed.